Effect of dietary phenylalanine restriction on visual attention span in mentally retarded subjects with phenylketonuria - Giffin, F D; Clarke, J T; d'Entremont, D M (Canadian journal of neurological sciences, 1980)
An ABA within-subject study design was used to assess the effect of dietary phenylalanine restriction on the visual attention span of three mentally retarded males (9, 15, and 21 years old) with phenylketonuria. Visual attention span was measured by recording the amount of time the subjects visually fixated pictures projected on a screen according to a standardized test protocol. After 4-6 weeks of baseline testing (A-phase), each subject was placed on a phenylalanine-restricted diet, designed to maintain plasma phenylalanine levels at 0.3-0.9 mM, for 8-14 weeks (B-phase). A return to baseline phenylalanine intake (A-phase) was achieved by surreptitiously adding sufficient L-phenylalanine to the therapeutic diets to increase plasma concentrations of the amino acid to pretreatment levels. Diet treatment (B-phase) was associated with highly significant improvements in visual attention span in two subjects (multivariate analysis of variance, P less than 0.001); the third subject, the most retarded, showed no effect. No objectively demonstrable change in behavior was documented in any subject. However, the results support the view that phenylalanine toxicity extends beyond early childhood and that some component of the toxicity is reversible, even in severely retarded patients with phenylketonuria.